2005
DOI: 10.2174/1566523053544218
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Bone Regeneration

Abstract: Efficacious bone regeneration could revolutionize the clinical management of many bone and musculoskeletal disorders. Bone has the unique ability to regenerate and continuously remodel itself throughout life. However, clinical situations arise when bone is unable to heal itself, as with segmental bone loss, fracture non-union, and failed spinal fusion. This leads to significant morbidity and mortality. Current attempts at improved bone healing have been met with limited success, fueling the development of impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 142 publications
3
118
0
3
Order By: Relevance
“…We previously demonstrated that BMP2, BMP6, and BMP9 can effectively upregulate OPN and OC expression in MSCs. 19,20,[24][25][26] As shown in Figure 4c, BMP2, BMP6, and BMP9 failed to induce any significant increases in OC expression in MG63, U2OS, and SaOS2 cells, although there was a small (o2.5-fold) but consistent induction of OPN expression in TE85 cells. Most OS lines, however, did not exhibit any significant increases in OPN expression upon osteogenic BMP stimulation (although there was a less than twofold increase in MG63 cells; Figure 4c).…”
Section: Osteogenic Bmps Upregulate the Expression Of Earlymentioning
confidence: 77%
See 3 more Smart Citations
“…We previously demonstrated that BMP2, BMP6, and BMP9 can effectively upregulate OPN and OC expression in MSCs. 19,20,[24][25][26] As shown in Figure 4c, BMP2, BMP6, and BMP9 failed to induce any significant increases in OC expression in MG63, U2OS, and SaOS2 cells, although there was a small (o2.5-fold) but consistent induction of OPN expression in TE85 cells. Most OS lines, however, did not exhibit any significant increases in OPN expression upon osteogenic BMP stimulation (although there was a less than twofold increase in MG63 cells; Figure 4c).…”
Section: Osteogenic Bmps Upregulate the Expression Of Earlymentioning
confidence: 77%
“…We previously demonstrated that BMP2 and BMP9 can effectively induce ALP activity in MSCs. 19,20,[24][25][26] Our preliminary results indicated that most, if not all, of the TGFb/BMP types I and II receptors were expressed in the tested OS lines (data not shown). The four OS lines were stimulated with BMP2, BMP9, or GFP control, and their ALP activities were measured at days 5, 7, and 10.…”
Section: Connective Tissue Growth Factor Is Highly Expressed In Uncommentioning
confidence: 86%
See 2 more Smart Citations
“…2,41 The majority of these studies have used adenoviral vectors to infect cells either ex vivo or in vivo. These vectors, however, elicit an immune response and have a limited duration of expression.…”
Section: Discussionmentioning
confidence: 99%